The coat protein p25 from maize chlorotic mottle virus involved in symptom development and systemic movement of tobacco mosaic virus hybrids - Zhang, Chao; Wang, Di; Li, Weimin; Zhang, Baolong; Abdel-Fattah Ouf, Gamal M.; Su, Xiaofeng; Li, Jun (Frontiers in Microbiology, 2022)
Viral coat protein (CP) has numerous critical functions in plant infection, but little is known about p25, the CP of maize chlorotic mottle virus (MCMV; Machlomovirus), which causes severe yield losses in maize worldwide. Here, we investigated the roles of p25 in pathogenicity and systemic movement, as well as potential interactions with host plants, using a hybrid tobacco mosaic virus (TMV)-based expression system. Highly conserved protein p25 is predicted to contain a membrane-anchored nuclear localization signal (NLS) sequence and an extracellular sequence. In transgenic Nicotiana benthamiana plants containing the movement protein (MP) of TMV (TMV-MP), p25 induced severe symptoms, including dwarf and foliar necrosis, and was detected in inoculated and non-inoculated leaves. After the deletion of NLS from nuclear-located p25, the protein was found throughout the host cell, and plant stunting and starch granule deformity were reduced. Systemic movement and pathogenicity were significantly impaired when the C-terminal regions of p25 were absent. Using virus-induced gene silencing (VIGS), the transcript level of heat shock protein HSP90 was distinctly lower in host plants in association with the absence of leaf necrosis induced by TMV-p25. Our results revealed crucial roles for MCMV p25 in viral pathogenicity, long-distance movement, and interactions with N. benthamiana.